Insomnia, Total Sleep Time and the 2D:4D Digit Ratio - Verster, Joris C.; Mackus, Marlou; van de Loo, Aurora J.A.E.; Garssen, Johan; Roth, Thomas (Current Psychopharmacology, 2017)
Background: Elevated levels of testosterone have been mentioned to affect sleep quality and increase the risk on developing insomnia. The second (index finger, 2D) to fourth (ring finger, 4D) digit ratio (2D:4D) is a biological correlate for prenatal testosterone and estrogen exposure. Objective: The objective of this study was to investigate the possible relationship between the 2D:4D digit ratio and insomnia, sleep quality, and total sleep time. Methods: A survey was held among N=557 Dutch students. In addition to demographic data, a subscale of the Dutch SLEEP-50 questionnaire was completed, assessing insomnia symptoms experienced over the past 4 weeks. For both hands, the 2D:4D ratio was assessed using digital Vernier calipers. Results: Data from N=143 men and N=366 women was analyzed. Their mean (SD) age was 20.8 (2.6). N=21 men and N=54 women scored above the cut-off point (≥ 19) for insomnia (average score 22.5 ± 3.4). Overall, no significant correlations were found between the digit ratio of either hand and insomnia, sleep quality, or total sleep time. In men, a significant correlation was found between the right 2D:4D ratio and total sleep time (r=0.173, p=0.039). No significant effects were found in women. Conclusion: No significant associations were found between the 2D:4D digit ratio and insomnia.
Keywords: digit ratio